Braess' paradox in the age of traffic information. Issue 3 (4th March 2021) - Bittihn, S; Schadschneider, A
Abstract: The Braess paradox describes the counterintuitive situation that the addition of new roads to road networks can lead to higher travel times for all network users. Recently we could show that user optima leading to the paradox exist in networks of microscopic transport models. We derived phase diagrams for two kinds of route choice strategies that were externally tuned and applied by all network users. Here we address the question whether these user optima are still realized if intelligent route choice decisions are made based upon two kinds of traffic information. We find that the paradox still can occur if the drivers (1) make informed decisions based on their own past experiences or (2) use traffic information similar to that provided by modern navigation apps. This indicates that modern traffic information systems are not able to resolve Braess' paradox.